Implementasi Peraturan Menteri Keuangan Nomor 168 Tahun 2023 Tentang Pph 21 Tarif Efektif Rata-Rata (Studi Kasus Pt Trinitax) - Kevin Parningotan Parhusip (Jurnal Ekonomi dan Bisnis Digital, 2024)
Every year the government wants to increase tax revenue, therefore the government always makes innovations to be able to make tax revenue bigger. One of them is by issuing the Regulation of the Minister of Finance Number 168 of 2023. This study was conducted to determine the implementation, constraints, and also the impacts that occur due to the Regulation of the Minister of Finance Number 168 of 2023. This study uses a qualitative method with a case study approach using data triangulation techniques as a data collection technique. As for data analysis techniques, this paper uses several methods, namely by transcribing data, reducing data, checking the validity of data, and drawing conclusions/verification. The results of this study indicate that the Implementation of the Minister of Finance Regulation Number 168 of 2023 concerning Income Tax 21 Average Effective Rates is implemented properly and correctly